Association Between Carotid Artery Perivascular Fat Density and Intraplaque Hemorrhage - Zhang, Shuai; Gu, Hui; Yu, Xinxin; Kang, Bing; Yuan, Xianshun; Wang, Ximing (Frontiers in Cardiovascular Medicine, 2021)
Objectives: Perivascular adipose tissue plays a key role in atherosclerosis, but its effects on the composition of carotid atherosclerotic plaques are unknown. This study aimed to investigate the association between inflammatory carotid artery with intraplaque hemorrhage (IPH) in the carotid artery. Methods: Carotid inflammation was assessed by perivascular fat density (PFD) in 72 participants (mean age, 65.1 years, 56 men) who underwent both computed tomography angiography (CTA) and magnetic resonance imaging (MRI) within 2 weeks. Presence of IPH was assessed with MRI. Carotid stenosis, maximum plaque thickness, calcification, and ulceration were evaluated through CTA. The association between PFD and the occurrence of IPH was studied using generalized estimating equations analysis. Results: Of 156 plaques, 72 plaques (46.2%) had IPH. Plaques with IPH shower higher PFD than those without (-41.4±3.9 HU versus -55.8±6.5 HU; P<0.001). After adjusting for age, calcification, degree of stenosis, maximum plaque thickness, and ulceration, PFD (OR, 1.96; 95% CI, 1.41–2.73; P<0.001) was found to be strongly associated with the presence of IPH. Conclusions: Higher PFD is associated with presence of IPH in the carotid artery. These findings may provide novel insights into the pathogenesis of IPH, and thus may serve as a guide in developing a new targeted therapy for IPH.